Pendampingan Sertifikasi Produk Halal pada UMKM Tempe di Kelurahan Plombokan Kota Semarang - Anitiyo Soelistiyono; Albert Albert; Moeljono Moeljono (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to accompany the halal certification process for Mr. Ngadinu's tempeh MSMEs on Jalan Mustokoweni, Plombokan Village, North Semarang District. This assistance is carried out because these MSMEs do not yet have a halal certificate, so they have not been able to increase production quantity and competitiveness in the market. Halal certification is an important factor for business actors in the food and beverage sector to guarantee halal products and increase consumer confidence. Tempe products that are not yet halal certified can raise doubts among the public, so obtaining halal certification is a strategic step to strengthen the product's image. The main objective of this program is to increase MSME players' understanding of the importance of halal certification and the process of obtaining it, assist in processing halal certification, ensure that tempe products meet halal standards and are of good quality, and expand market share through the attraction of halal certification. The method applied in this program is halal certification assistance, which includes three main stages: (1) preparation stage, which includes pre-survey, observation, discussion and documentation; (2) implementation stage, in the form of direct assistance in the halal certification process; and (3) the stage of reporting activity results. Through this program, it is hoped that tempe MSMEs can understand the importance of halal certification, know the procedures for obtaining it, and be able to increase the competitiveness of their products in the market.